Pelatihan Fotografi Dasar bagi Pelaku UMKM Kabupaten Pamekasan - Badrut Tamami, Novi Diana; Samlawi, Achmad K; Qur’ana, Nurul; Jufri, Jufri; Romadhon, Agus (Jurnal Ilmiah Pangabdhi, 2025)
In the industrial world or what we could call the modern world, it is not only factories or companies that are developing but also MSMEs. MSMEs are enterprises or businesses carried out by individuals, groups, small business entities, or households. Indonesia as a developing country makes MSMEs the main foundation of the community's economic sector, this is done to encourage the ability to be independent in development in society, especially in the economic sector. This MSME has also implemented technology in its business processes. In technological advances, society is required to be able to apply technology, especially the internet, such as electronic market share, e- market ethics, and e-market advertising. The core subjects of e-market advertising are product photography and product design. Because technology has developed nowadays, all the above processes can be done through it. This training is specifically designed for this purpose, namely to develop the skills of the MSME community in smartphone product photography and how to package their products so that they can compete and win the competition in the electronics market. This training was quite successful as shown by the enthusiasm of the training participants and resulted in some very good product photography. The result of this training is that more and more SME practitioners are going online and promoting their products in mass media.